Penerapan Pembelajaran Project Based Learning dalam Fiqh untuk pembiasaan Ubudiyah di MA Al Hikam Diwek Jombang. - Faizah, Nur; Umam, Khoirul; Rofiq, Wulida (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
Learning Fiqh in Islamic Senior High Schools (Madrasah Aliyah/MA) often faces a gap between theoretical understanding and practical worship (ubudiyah), where students struggle to internalize the values of worship in their daily lives. The research question posed is: How does the application of the Project Based Learning (PBL) model in Fiqh subjects improve the ubudiyah habits of students at MA Al Hikam Diwek Jombang? This study uses a qualitative approach with a case study design at MA Al Hikam Diwek Jombang, East Java. Data were collected through participant observation, in-depth interviews with teachers and students, and analysis of curriculum documents. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that PBL successfully enhanced students' discipline and intrinsic awareness, with 85% of participants able to accurately explain the conditions for valid worship. However, unequal participation in group work and limited resources remain major challenges. The novelty of this research lies in the integration of PBL with daily worship practices (e.g., documenting congregational prayers), which has not been explored in previous studies.